A metal-organic cage complex mixed matrix membrane for gas separation and its preparation method and application

Through the combination of zirconium-based porous metal-organic cage complex ZRT-1-2OH and polyimide, the problem of insufficient performance of metal-organic cage materials in the prior art under low filling amount is solved, and high CO2/ CH4 is separated and selectively and broadens the scope of application.

CN116059837BActive Publication Date: 2024-12-17BEIJING UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310088093.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-09
Publication Date
2024-12-17
Estimated Expiration
2043-02-09

AI Technical Summary

Technical Problem

It is difficult for existing metal-organic cage materials to achieve high permeability and high selectivity at the same time under low filling conditions, and the adsorption of carbon dioxide is low, affecting the separation selectivity of the CO2/CH4 mixed gas.

Method used

The mixed matrix membrane is synthesized with zirconium-based porous metal-organic cage complex ZRT-1-2OH and polyimide. By optimizing reaction conditions and solvent selection, the filling amount is reduced and CO2 adsorption amount is increased, and the separation of CO2/CH4 is enhanced. Selective.

Benefits of technology

The separation selectivity of CO2/CH4 is significantly improved under lower load conditions, and the excellent performance is maintained after the increase in filling amount, exceeding the Robeson upper limit and broadening the application range of hybrid matrix membranes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116059837B_ABST
    Figure CN116059837B_ABST
Patent Text Reader

Abstract

The present invention discloses a metal-organic cage complex mixed matrix membrane for gas separation and its preparation method and application. It relates to the fields of material science and gas separation. The mixed matrix membrane comprises a high molecular polymer and a porous metal-organic cage complex ZRT-1-2OH. The porous metal-organic cage complex ZRT-1-2OH filled in the mixed matrix membrane of the present invention is different from the traditional inorganic filling material. The traditional inorganic filling material has better separation performance as the filling amount in the mixed matrix membrane increases; while the porous metal-organic cage complex ZRT-1-2OH prepared by the present invention has the best separation performance of the membrane at a lower filling amount (2.17wt%), and then as its filling amount increases, the separation performance of the membrane decreases. The mixed matrix membrane of the present invention can be applied to the separation of various gases, and has broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the fields of material science and gas separation, and in particular to a metal-organic cage complex mixed matrix membrane for gas separation and a preparation method and application thereof. Background Art

[0002] Gas separation has become a vital link in today's chemical production, energy production, carbon capture and storage, but the existing gas separation technology is mainly heat-driven separation, which will consume a lot of energy. Membrane separation technology is considered to be a very promising option in the field of gas separation because it does not require heat-driven phase change, has low energy consumption, low cost and continuous operation. Separation membranes can be divided into organic polymer membranes and inorganic material membranes according to the material of the membrane. Organic polymer membranes dominate the field of separation membranes due to their advantages in cost-effectiveness and scalable manufacturing, but they still face the problem of "trade-off" effect (i.e., they cannot achieve high permeability and high selectivity at the same time, also known as Robson upper limit). Inorganic material membranes have also been widely studied and developed in the field of gas separation due to their excellent gas separation performance, but they are costly, fragile, have poor reproducibility, and are difficult to prepare on a large scale.

[0003] Mixed matrix membranes (MMMs) are separation membranes made of a continuous polymer matrix and discrete organic / inorganic filler materials, which combine the easy processability of polymers with the high permeability and selectivity of fillers. Among the existing mixed matrix membranes, common inorganic / organic fillers include zeolites, silica, alumina; carbon nanotubes, carbon molecular sieves, graphene oxide; metal-organic framework materials (MOFs), covalent-organic framework materials (COFs), and metal-organic cages (MOCs). Zeolites, silica, alumina, and graphite materials have become the earliest fillers used to prepare MMMs due to their simple preparation, good stability, and excellent performance. However, inorganics have poor compatibility with organic polymers, which often leads to defects such as pinholes and cage-in-net structures, reducing the gas selectivity of the obtained MMMs. MOFs and COFs materials are emerging porous crystalline materials with uniform 2D or 3D interconnected channels. They have good compatibility with organic polymers. However, their particles are not easy to disperse in the casting solution, which leads to their aggregation in the polymer matrix, especially at high loading levels. This agglomeration phenomenon makes it difficult for MOFs pores to exert their advantages, which in turn affects the separation performance of the membrane. The casting solution composed of metal-organic cage (MOCs) materials and polymers has good uniformity, which to a certain extent avoids the aggregation of fillers in mixed matrix membranes. However, the existing metal-organic cage materials used to prepare mixed matrix membranes have few optional types and require a high filling amount. Therefore, how to design metal-organic cage (MOCs) materials so that they can exert high permeability and high selectivity of the membrane under low filling conditions is a technical problem that needs to be solved urgently in this field.

[0004] At present, the related patent of zirconium-based metal-organic cage mixed matrix membrane (CN113828170A) reports that the mixed matrix membrane prepared under low loading conditions has excellent separation performance, but the zirconium-based metal-organic cage in the invention has the defect of low adsorption of carbon dioxide in the adsorption test, which makes the mixed matrix membrane have poor separation selectivity for CO2 / CH4 mixed gas. Therefore, it is still meaningful to continue to explore uniform mixed matrix membranes with lower loading and better separation performance. Summary of the invention

[0005] The purpose of the present invention is to provide a metal-organic cage complex mixed matrix membrane for gas separation and its preparation method and application, so as to solve the problems existing in the above-mentioned prior art and reduce the filling amount of the metal-organic cage material while ensuring the performance of the mixed matrix membrane.

[0006] To achieve the above object, the present invention provides the following solutions:

[0007] One of the technical solutions of the present invention is a novel polymer-metal organic cage mixed matrix membrane, wherein the mixed matrix membrane comprises a polymer and a porous metal-organic cage complex ZRT-1-2OH.

[0008] Furthermore, the content of the porous metal-organic cage complex ZRT-1-2OH in the mixed matrix membrane is 0.4-10 wt %.

[0009] Furthermore, the preparation method of the porous metal-organic cage complex ZRT-1-2OH comprises the following steps:

[0010] Zirconocene, dihydroxyterephthalic acid, N,N-dimethylacetamide, formic acid and water are mixed and dissolved, reacted at 55-85° C. for 8-12 hours, purified and dried to obtain the porous metal-organic cage complex ZRT-1-2OH.

[0011] Furthermore, the high molecular polymer is polyimide.

[0012] The second technical solution of the present invention is a method for preparing the novel polymer-metal organic cage mixed matrix membrane, comprising the following steps:

[0013] The high molecular polymer, the porous metal-organic cage complex ZRT-1-2OH and an organic solvent are mixed and dissolved to obtain a casting solution, and a membrane is prepared and dried to obtain the mixed matrix membrane.

[0014] Furthermore, the organic solvent is dimethyl sulfoxide, N,N-dimethylformamide, or N,N-dimethylacetamide.

[0015] Furthermore, the drying temperature is 65-120° C. and the drying time is 12-24 hours.

[0016] The purpose of drying is to evaporate all organic solvents.

[0017] Furthermore, the mass volume ratio of the high molecular polymer, the porous metal-organic cage complex ZRT-1-2OH and the organic solvent is 45 mg: 0.2-5 mg: 10 mL.

[0018] The third technical solution of the present invention is the application of the above-mentioned mixed matrix membrane in gas separation.

[0019] Furthermore, the gas separation system comprises at least two of hydrogen, oxygen, nitrogen, carbon dioxide, methane, sulfur dioxide, hydrogen sulfide, ethylene, ethane, propylene and propane.

[0020] The technical concept of the present invention is as follows:

[0021] Zirconium-based metal-organic cage materials have excellent stability and strong Zr-O coordination bonds, and their ligand modifiability, reasonable solubility and permanent porosity have received much attention in the field of gas adsorption separation. The present invention uses zirconium-based metal-organic cage complex ZRT-1-2OH and polyimide to prepare mixed matrix membranes, and obtains higher CO2 / CH4 separation selectivity under lower loading conditions. ZRT-1-2OH is composed of trinuclear zirconocene clusters (Cp3Zr3O(OH)3 (Cp: cyclopentadienyl) and 2,5-dihydroxyterephthalic acid, and has a regular tetrahedral geometric structure. It exhibits good solubility in dimethyl sulfoxide, N,N-dimethylformamide, and N,N-dimethylacetamide. As a filler for mixed matrix membranes, it has a higher adsorption capacity for carbon dioxide, further improving the separation performance of mixed matrix membranes for CO2 / CH4.

[0022] The present invention discloses the following technical effects:

[0023] (1) The present invention prepares a new zirconium-based metal-organic cage material ZRT-1-2OH, which has a high adsorption capacity for carbon dioxide, further improving the separation selectivity of the mixed matrix membrane for CO2 / CH4 mixed gas, and at the same time achieving excellent separation performance under conditions of lower loading (2.17wt%). Subsequently, as its filling amount increases, the separation performance of the membrane decreases.

[0024] (2) The mixed matrix membrane prepared by the present invention is formed by doping a high molecular polymer with a porous metal-organic cage complex and has the characteristic of a simple structure.

[0025] (3) The novel porous metal-organic cage complex ZRT-1-2OH prepared by the present invention is a zero-dimensional functional complex with good dispersibility; a mixed matrix membrane is prepared by introducing the porous metal-organic cage complex ZRT-1-2OH material into an organic polymer solution, and the preparation method is simple.

[0026] (4) The present invention is of great significance for improving the application scope of membrane separation technology (such as gas separation) and broadening the types of mixed matrix membranes, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0028] Figure 1This is the N2 adsorption diagram of the porous metal-organic cage complex ZRT-1-2OH prepared in Example 1 at 77K;

[0029] Figure 2 This is the CO2 / CH4 adsorption diagram of the porous metal-organic cage complex ZRT-1-2OH prepared in Example 1 at room temperature;

[0030] Figure 3 XRD and ESI-TOF-MS images of the porous metal-organic cage complex ZRT-1-2OH prepared in Example 1;

[0031] Figure 4 This is the SEM image of the mixed matrix membrane prepared in Example 4. DETAILED DESCRIPTION

[0032] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0033] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0034] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0035] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0036] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0037] The "room temperature" described in the present invention is within the range of 20 to 30°C unless otherwise specified.

[0038] The high molecular polymer 6FDA-DAM (polyimide) used in the embodiment of the present invention is synthesized by purified 6FDA (hexafluorodianhydride) and DAM (mesitylene diamine) and solvent NMP (N-methylpyrrolidone), which belongs to conventional technical means in the field and will not be repeated here. Other high molecular polymers 6FDA-DAM obtained through commercial channels can also achieve the technical effects of the present invention.

[0039] Example 1 Preparation of Porous Metal-Organic Cage Complex ZRT-1-2OH

[0040] 2.4 g zirconocene, 2.4 g dihydroxyterephthalic acid and 20 mL N, N-dimethylacetamide (DMA) were mixed and ultrasonicated until dissolved; then 100 mL formic acid was added and ultrasonicated until mixed evenly, and finally 1 mL ultrapure water was added; the reaction solution was then placed in a 65°C oven for 8 h to react, and after the reaction was completed, the reaction solution was cooled and centrifuged (a large amount of yellow powder was formed during the reaction), and the obtained solid was washed three times with N, N-dimethylacetamide (DMA) and dichloromethane in turn, and finally dried under vacuum conditions at 65°C to obtain a porous metal-organic cage complex ZRT-1-2OH.

[0041] Results: The N2 adsorption graph of the porous metal-organic cage complex ZRT-1-2OH prepared in this example at 77K is as follows: Figure 1 shown by Figure 1 It can be seen that the prepared ZRT-1-2OH has a microporous structure.

[0042] The CO2 / CH4 adsorption diagram of the porous metal-organic cage complex ZRT-1-2OH prepared in this example at room temperature is as follows Figure 2 shown by Figure 2 It can be seen that ZRT-1-2OH has a higher adsorption capacity for CO2 at room temperature, and the CO2 absorption rate is significantly greater than the CH4 absorption rate, indicating that ZRT-1-2OH has a higher CO2 affinity.

[0043] The XRD and ESI-TOF-MS images of the porous metal-organic cage complex ZRT-1-2OH prepared in this example are as follows: Figure 3 shown by Figure 3 It can be seen that ZRT-1-2OH was successfully synthesized.

[0044] Example 2 Preparation of Porous Metal-Organic Cage Complex ZRT-1-2OH

[0045] 2.4 g zirconocene, 2.4 g dihydroxyterephthalic acid and 20 mL N, N-dimethylacetamide (DMA) were mixed and ultrasonicated until dissolved; then 100 mL formic acid was added and ultrasonicated until mixed evenly, and finally 1 mL ultrapure water was added; the reaction solution was then placed in a 55°C oven for 12 h to react, and after the reaction was completed, the reaction solution was cooled and centrifuged (a large amount of yellow powder was formed during the reaction), and the obtained solid was washed three times with N, N-dimethylacetamide (DMA) and dichloromethane in turn, and finally dried at 65°C under vacuum conditions to obtain a porous metal-organic cage complex ZRT-1-2OH.

[0046] Example 3 Preparation of Porous Metal-Organic Cage Complex ZRT-1-2OH

[0047] 2.4 g zirconocene, 2.4 g dihydroxyterephthalic acid and 20 mL N, N-dimethylacetamide (DMA) were mixed and ultrasonicated until dissolved; then 100 mL formic acid was added and ultrasonicated until mixed evenly, and finally 1 mL ultrapure water was added; the reaction solution was then placed in an 85°C oven for 9 hours to react. After the reaction was completed, the reaction solution was cooled and centrifuged (a large amount of yellow powder was formed during the reaction), and the obtained solid was washed three times with N, N-dimethylacetamide (DMA) and dichloromethane in turn, and finally dried under vacuum conditions at 65°C to obtain a porous metal-organic cage complex ZRT-1-2OH.

[0048] Example 4 Preparation of mixed matrix membrane

[0049] Take 1 mg of the porous metal-organic cage complex ZRT-1-2OH prepared in Example 1 and add it to 10 mL of dimethyl sulfoxide (DMSO) and sonicate until it dissolves; then add 45 mg of high molecular polymer 6FDA-DAM and sonicate until it dissolves to obtain a mixed matrix membrane casting solution; pour the mixed matrix membrane casting solution into a circular watch dish with a radius of 2.25 cm, and then put it into a 100°C oven for 22 hours (to allow the solvent to evaporate completely) to obtain a yellow transparent mixed matrix membrane.

[0050] Results: The filling amount of the porous metal-organic cage complex ZRT-1-2OH in the mixed matrix membrane prepared in this example is 2.17wt%; under the test conditions of 25℃ and 0.2MPa, the CO2 permeability coefficient can reach 1498.21barrer, and the CO2 / CH4 selectivity is 23, which exceeds the Robeson upper limit of CO2 / CH4 in 2008.

[0051] The SEM image of the mixed matrix membrane prepared in this example is as follows Figure 4 shown by Figure 4 It can be seen that the mixed matrix membrane prepared in this example is a simple structure in which a high molecular polymer and a porous metal-organic cage complex are doped with each other.

[0052] Example 5 Preparation of mixed matrix membrane

[0053] The same as Example 4, the only difference is that the added amount of the porous metal-organic cage complex ZRT-1-2OH is 0.2 mg.

[0054] Results: The filling amount of the porous metal-organic cage complex ZRT-1-2OH in the mixed matrix membrane prepared in this example is 0.44wt%; under the test conditions of 25℃ and 0.2MPa, the CO2 permeability coefficient can reach 991.41barrer and the CO2 / CH4 selectivity is 19.22.

[0055] Example 6 Preparation of mixed matrix membrane

[0056] The same as Example 1, the only difference is that the amount of the porous metal-organic cage complex ZRT-1-2OH added is 2 mg; and the mixture is placed in an oven at 100° C. for 19 hours.

[0057] Results: The filling amount of the porous metal-organic cage complex ZRT-1-2OH in the mixed matrix membrane prepared in this example is 4.26wt%; under the test conditions of 25℃ and 0.2MPa, the CO2 permeability coefficient can reach 1217.25barrer, and the CO2 / CH4 selectivity is 21.39.

[0058] Example 7

[0059] Preparation of mixed matrix membranes

[0060] The same as Example 1, the only difference is that the amount of the porous metal-organic cage complex ZRT-1-2OH added is 5 mg; put into an oven at 100° C. for 24 hours.

[0061] Results: The filling amount of the porous metal-organic cage complex ZRT-1-2OH in the mixed matrix membrane prepared in this example is 10wt%; under the test conditions of 25℃ and 0.2MPa, the CO2 permeability coefficient can reach 1178.50barrer and the CO2 / CH4 selectivity is 20.77.

[0062] Comparative Example 1

[0063] The same as Example 4, the only difference is that the addition of the porous metal-organic cage complex ZRT-1-2OH is omitted, and a pure high molecular polymer membrane is prepared.

[0064] Results: The pure polymer membrane prepared in this comparative example does not contain inorganic materials; under the test conditions of 25°C and 0.2MPa, the CO2 permeability coefficient can reach 1058.30 barrer, and the CO2 / CH4 selectivity is 19.16, which is lower than the Robeson upper limit of CO2 / CH4 in 2008. By comparing this comparative example with Example 4, it can be seen that after the porous metal-organic cage complex ZRT-1-2OH is introduced into the polymer membrane, its flux and selectivity are greatly improved.

[0065] Comparative Example 2

[0066] The same as Example 4, the only difference is that the added amount of the porous metal-organic cage complex ZRT-1-2OH is 10 mg.

[0067] Results: The filling amount of the porous metal-organic cage complex ZRT-1-2OH in the mixed matrix membrane prepared in this comparative example is 18.18wt%; under the test conditions of 25℃ and 0.2MPa, the CO2 permeability coefficient can reach 897.29barrer, and the CO2 / CH4 selectivity is 19.9, which is lower than the Robeson upper limit of CO2 / CH4 in 2008.

[0068] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. Application of a polymer-metal organic cage mixed matrix membrane in gas separation, characterized in that: The gas separation system comprises carbon dioxide and methane; The mixed matrix membrane includes a high molecular polymer and a porous metal-organic cage-like complex ZRT-1-2OH; the content of the porous metal-organic cage-like complex ZRT-1-2OH in the mixed matrix membrane is 2.17 wt%; The preparation method of the metal-organic cage complex ZRT-1-2OH comprises the following steps: dissolving zirconocene, dihydroxyterephthalic acid, N,N-dimethylacetamide, formic acid and water, reacting at 55-85° C. for 8-12 hours, purifying and drying to obtain the porous metal-organic cage complex ZRT-1-2OH; The preparation method of the polymer-metal organic cage mixed matrix membrane comprises the following steps: mixing and dissolving the polymer, the porous metal-organic cage complex ZRT-1-2OH and an organic solvent to obtain a casting solution, forming a membrane, and drying to obtain the mixed matrix membrane.

2. The use according to claim 1, characterized in that: The high molecular polymer is polyimide.

3. The use according to claim 1, characterized in that: The organic solvent is one or more of dimethyl sulfoxide, N,N-dimethylformamide, and N,N-dimethylacetamide.

4. The use according to claim 1, characterized in that: The drying temperature is 65-120° C. and the drying time is 12-24 hours.

5. The use according to claim 1, characterized in that: The mass volume ratio of the high molecular polymer, the porous metal-organic cage complex ZRT-1-2OH and the organic solvent is 45 mg: 1 mg: 10 mL.